2021
DOI: 10.3390/cancers13092149
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of the Role of Diet and Lifestyle Factors in the Development and Prevention of Endometrial Cancer

Abstract: Endometrial cancer is the most common cancer affecting the reproductive organs of women living in higher-income countries. Apart from hormonal influences and genetic predisposition, obesity and metabolic syndrome are increasingly recognised as major factors in endometrial cancer risk, due to changes in lifestyle and diet, whereby high glycaemic index and lipid deposition are prevalent. This is especially true in countries where micronutrients, such as vitamins and minerals are exchanged for high calorific diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 373 publications
(430 reference statements)
1
28
0
1
Order By: Relevance
“…Obesity leads to diseases such as abnormal lipid metabolism and hyperlipidemia [ 59 ], and is an important risk factor for carcinogenesis. Some studies have demonstrated that improvement of blood lipid levels and obesity control reduced the occurrence rate of GC, colorectal cancer, and esophageal cancer [ 60 62 ]. Abnormal lipid metabolism triggers a cascade of molecular events to finally cause malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity leads to diseases such as abnormal lipid metabolism and hyperlipidemia [ 59 ], and is an important risk factor for carcinogenesis. Some studies have demonstrated that improvement of blood lipid levels and obesity control reduced the occurrence rate of GC, colorectal cancer, and esophageal cancer [ 60 62 ]. Abnormal lipid metabolism triggers a cascade of molecular events to finally cause malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, several prophylactic measures, albeit less specific, that may substitute existing causal preventive procedures. 2 Prophylactic measures in endometrial cancer include healthy lifestyle (physical activity, no smoking, weight loss, fruits, vegetables, and vitamins, reduction of consumption of fat and protein), medical surveillance (obesity, diabetes, metabolic syndrome, hyperestrogenism, genetic factors, hormonal preventive therapy) and, if genetically justified, even prophylactic hysterectomy [ 181 , 182 ]. 3 In ovarian cancer, improvement of healthy lifestyle by similar means as in EC can be helpful.…”
Section: Figurementioning
confidence: 99%
“…It develops from proliferation caused by the stimulation, not balanced by progesterone or other progestogens, of the endometrium by endogenic (similarly to obesity) or exogenic oestrogens (during systemic monotherapy in women with a preserved uterus). Other risk factors relevant to this type of cancer include childlessness, early menarche and late menopause, long-term therapy with drugs from the group of selective oestrogen receptor modulators, diabetes, hypertension, and certain genetic syndromes [ 7 , 8 , 9 ]. Type 2 endometrial cancer is responsible for the remaining 20% of cases and includes poorly differentiated endometrioid cancers (G3) as well as serous, clear-cell, mucinous, squamous, and other tumours.…”
Section: Introductionmentioning
confidence: 99%